High-resolution structured illumination solid immersion fluorescence microscopy - Wang, Lin (2010)
The use of aplanatic solid immersion lenses (ASILs) made of high refractive index optical glasses provides a route to wide-field high-resolution optical microscopy. Structured illumination microscopy (SIM) can double the spatial bandwidth of a microscope to achieve high-resolution imaging. This research aims to investigate the combination of the ASILs and SIM in fluorescence microscopy, which we call structured illumination solid immersion fluorescence microscopy (SISIM), to pursue a microscopic system with very large numerical aperture and high lateral resolution. The first stage of the research shows the development of solid immersion fluorescence microscopy (SIF) employing an ASIL allows us to obtain a fluorescence microscope with effective numerical aperture of 1.85. The aberration issues, especially chromatic aberration, that need to be circumvented are analysed by both optical simulation and experimental verification. The near-field imaging property is also discussed and demonstrated. Then the SIM using a diffraction grating to generate structured illumination pattern via two-beam interference is developed. Finally, the SISIM system is constructed by combining the structured illumination with the SIF, and an effective numerical aperture of 3 has been obtained. Future developments of the SISIM system to make it achieve higher resolution and suit routine use are proposed. SISIM is a promising high-resolution microscopic technique with extensive potential applications in cell biology.